Differentiation of Phytophthora boehmeriae and P. capsici isolates associated with foliar blight of chilli using protein and isozyme profiles - K.V. PAVANI, S. MADHURA, P. CHOWDAPPA* and (Indian Phytopathology, 2016)
Phytophthora blight caused by Phytophthora capsici Leonian is a major threat to pepper production and is ranked as the second most devastating disease worldwide. P. capsici causes a root and crown rots, as well as an aerial blight of leaves, fruit, and stems, on pepper. Recent studies showed that P. boehmeriae has emerged as a dominant pathogen in addition to P. capsici in causation of severe leaf blight epidemics on hot pepper in South India, although it is not serious pathogen of other crops in any part of the world. Phytophthora isolates (10), recovered from blight-affected leaf tissues of hot pepper from different localities of South India between 2011 and 2014 were evaluated using native and SDS-dissociated protein, and superoxide dismutase, malate dehydrogenase and malic enzyme isozyme patterns. P. boehmeriae and P. capsici isolates exhibited characteristic protein as well as isozyme profiles but isolates within a species are identical. Thus, the present study demonstrated that protein and isozyme profiles can be successfully employed in distinguishing species of Phytophthora encountered on hot pepper.